Methodology for Locale-Scale Monitoring for the PROTHEGO project: The Choirokoitia case study - Themistocleous, Kyriacos; Agapiou, Athos; Cuca, Branka; Danezis, Chris; Cigna, Francesca; Margottini, Claudio; Spizzichino, Daniele (My University, 2016)
© 2016 SPIE. PROTHEGO (PROTection of European Cultural HEritage from GeO-hazards) is a collaborative research project funded in the framework of the Joint Programming Initiative on Cultural Heritage and Global Change (JPICH) - Heritage Plus in 2015-2018 (www.prothego.eu). PROTHEGO aims to make an innovative contribution towards the analysis of geohazards in areas of cultural heritage, and uses novel space technology based on radar interferometry (InSAR) to retrieve information on ground stability and motion in the 400+ UNESCO's World Heritage List monuments and sites of Europe. InSAR can be used to measure micro-movements to identify geo-hazards. In order to verify the InSAR image data, field and close range measurements are necessary. This paper presents the methodology for local-scale monitoring of the Choirokoitia study site in Cyprus, inscribed in the UNESCO World Heritage List, and part of the demonstration sites of PROTHEGO. Various field and remote sensing methods will be exploited for the local-scale monitoring, static GNSS, total station, leveling, laser scanning and UAV and compared with the Persistent Scatterer Interferometry results. The in-situ measurements will be taken systematically in order to document any changes and geo-hazards that affect standing archaeological remains. In addition, ground truth from in-situ visits will provide feedback related to the classification results of urban expansion and land use change maps. Available archival and current optical satellite images will be used to calibrate and identify the level of risk at the Cyprus case study site. The ground based geotechnical monitoring will be compared and validated with InSAR data to evaluate cultural heritage sites deformation trend and to understand its behaviour over the last two decades.
Keywords: Cultural heritage; InSAR; Laser scanner; Natural hazards; Remote sensing; UAV